R&D decisions and productivity growth: Evidence from Switzerland and the Netherlands - Sabien Dobbelaere; Michael D. König; Andrin Spescha; Martin Wörter (Tinbergen Institute, 2023)
The fraction of R&D active firms decreased in Switzerland but increased in the Netherlands from 2000-2016. This paper examines reasons for this divergence and its impact on productivity growth. Our micro-data reveal R&D concentration among high-productivity firms in Switzerland. Innovation support sustains firms' R&D activities in both countries. Our structural growth model identifies the impact of innovation, imitation and R&D costs on firms' R&D decisions. R&D costs gained importance in Switzerland but not in the Netherlands, explaining the diverging R&D trends. Yet, counterfactual analyses show that policies should prioritize enhancing innovation and imitation success over cost reduction to boost productivity growth.
Keywords: D22; O31; O47; O52; 330; R&D; innovation; imitation; R&D costs; policy; productivity growth; traveling wave